If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(3-x)=3(2-x)
We simplify the equation to the form, which is simple to understand
2(3-x)=3(2-x)
Reorder the terms in parentheses
+(+6-2x)=3*(2-x)
Remove unnecessary parentheses
+6-2x=+3+*(+2-x+)
Reorder the terms in parentheses
+6-2x=+(+6-3x)
Remove unnecessary parentheses
+6-2x=+6-3x
We move all terms containing x to the left and all other terms to the right.
-2x+3x=+6-6
We simplify left and right side of the equation.
+1x=0
We divide both sides of the equation by 1 to get x.
x=0
| (x+8)(x-9)= | | 9x+5=11x-25 | | 5w=3+2w | | 4y-4=X-20 | | -6r=3r+18 | | 6m=6 | | 5d-4=3d+7 | | y=-4+0.25x | | 2/3(x-2)=16 | | 15+5y=90 | | (6x+7)+(7x+3)=180 | | 4x-9x+49=4x+31 | | 8-b=-7+4b | | 9(x-4)=5x-28 | | 7x+x=4x-2 | | 2r^3+15r^2=r^4 | | 2/3(3-x)=3(2-x) | | s^2=49 | | 6y-3y+9=4y+15 | | 4p-2=3p | | -4k+8=8k-16 | | h(-4)=5-4+5 | | 5t+6-2t-11= | | -9Y(3X+9y)= | | 103-w=160 | | 9-0=x | | -4+4r=12+5r+r | | 2y+3/2=1-y | | 9+3x=-18 | | -8.4-5.6=4y+0.7-3y | | 2(x+1)-3(4x-2)=6x | | 9-3d=9d-15 |